Review of recent developments and induced damage assessment in the modelling of the machining of long fibre reinforced polymer composites. (15th May 2020) - Cepero-Mejías, F.; Curiel-Sosa, J.L.; Blázquez, A.; Yu, T.T.; Kerrigan, K.; Phadnis, V.A.
Abstract: This manuscript offers a comprehensive review of the state of art on the machining induced damage modelling of long fibre reinforced polymers (LFRP), focusing on the two most common simulated machining operations, orthogonal cutting and drilling. A novel and critical discussion of composite damage modelling techniques used in machining works is offered, yielding numerous insights; advantages and disadvantages of current numerical techniques as well as possible improvements are included. Additionally, computational findings achieved so far in the literature are analysed in detail to allow remark of the current scope in the machining of LFRP laminates. Despite ingenious numerical solutions having been generated by previous authors to face the complex problems involve with the simulation of composite machining, the numerical capabilities to model the machining induced damage are still limited. Hence, different numerical strategies should be considered in future computational studies to enhance the reliability of current finite element models. The use of advanced continuum damage mechanics (CDM) approaches inserted via user-defined subroutines or the use of other computationally advanced methods such as eXtended Finite Element Method (XFEM) or phase field methods (PFM) to model composite fracture are recommended to improve the quality of numerical predictions.